Sustainable Management of the Municipal Solid Waste Resource Potential in the Context of Product Lifecycle Continuity - TELIZHENKO, Oleksandr; SHEVCHENKO, Тetiana; MISHENINA, Galyna (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016, 2017)
The theoretical foundations of sustainable management of municipal solid waste resource potential that covers the entire product life cycle are developed. The proposed management system of resource potential this waste is aimed simultaneously at its forming and using and is intended essentially for creating the necessary economic, environmental and technical pre-requisites for the transition of waste into the category of material resources.